Leaders of Collaboration, Communication, and Confidence Behind Adversity - Eileen May Atienza (Advanced Qualitative Research, 2023)
This study investigated the lived experience of public elementary school principals concerning the challenges encountered in professional and training needs in the new normal. The research design used was qualitative with phenomenology as an approach. Using the interpretative phenomenological approach, the study generated ten superordinate themes. Based on the consolidated findings and reflections, the study recommends that the Schools Division of Calamba City may focus on the provision of technical assistance, mentoring, and coaching to the school heads in crafting and formulating professional development activities intended for the challenges and issues encountered by the teachers from the classroom setting to the school set-up. In addition, School heads may provide different professional development activities aside from the monthly school-based learning action cell session. Teachers may provide feedback and suggestions to their school heads in dealing with their needs in the classroom and school as their second home. Future researchers who plan to investigate the same topic may use this as one of their references. Other factors which may influence the implementation of professional development training may be subjected to future studies. More so, other appropriate methods and designs may also be used to further validate this study's findings.